Social Media and Social Order - Herbert, David; Fisher-Høyrem, Stefan (De Gruyter, 2022)
This book addresses the relationship between social media and social order at multiple scales and sites, from city neighborhoods to national politics, to how the data harvested by transnational corporations influence lives worldwide. It provides insights into how diverse social worlds are being reshaped by social media, analysis of what this means, and reflection on how critical publics might constructively respond.